The Synchrotron Radiation for Steel Research - Piyada Suwanpinij (Advances in Materials Science and Engineering, 2016)
The synchrotron X-ray radiation is a great tool in materials characterization with several advantageous features. The high intensity allows clear interaction signals and high energy of X-ray yields higher sampling volume. The samples do not need extra preparation and the microstructure is therefore not affected. With the tunability of the X-ray energy, a large range of elements and features in the samples can be investigated by different techniques, which is a significant difference between a stand-alone X-ray tube and synchrotron X-ray. Moreover, any experimental equipment can be installed through which the synchrotron beam travels. This facilitates the so-called in situ characterization such as during heat treatment, hot deformation, chemical reaction or welding. Although steel which possesses rather high density requires very high energy X-ray for large interaction volume, lower energy is still effective for the investigation of local structure of nanoconstituents. This work picks up a couple examples employing synchrotron X-ray for the characterization of high strength steels. The first case is the quantification of precipitates in high strength low alloyed (HSLA) steel by X-ray absorption spectroscopy. The other case is the in situ X-ray diffraction for phase fraction and carbon partitioning in multiphase steels such as transformation induced plasticity (TRIP) steel.